2013
DOI: 10.1128/jvi.02476-12
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing, Annotation, and Characterization of the Influenza Ferret Infectome

Abstract: h Ferrets have become an indispensable tool in the understanding of influenza virus virulence and pathogenesis. Furthermore, ferrets are the preferred preclinical model for influenza vaccine and therapeutic testing. Here we characterized the influenza infectome during the different stages of the infectious process in ferrets with and without prior specific immunity to influenza. RNA from lung tissue and lymph nodes from infected and naïve animals was subjected to next-generation sequencing, followed by de novo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 48 publications
8
46
0
Order By: Relevance
“…The in vivo cytokine profiles following infection with A(H1N1) pdm09 virus presented in this study are consistent with those in other studies using the SYBR green real-time PCR assay and microarrays in ferrets (14,15,22,23,(38)(39)(40). Similar cytokine and chemokine profiles have also been detected in plasmas from children infected with A(H1N1)pdm09 virus (41), autopsy tissues from fatal cases of A(H1N1)pdm09 virus infection (42), and the lungs of pigs (43) This study demonstrated a remarkable consistency in the cytokine and chemokine patterns in the URT following infection with seasonal influenza A and B viruses.…”
Section: Discussionsupporting
confidence: 91%
“…The in vivo cytokine profiles following infection with A(H1N1) pdm09 virus presented in this study are consistent with those in other studies using the SYBR green real-time PCR assay and microarrays in ferrets (14,15,22,23,(38)(39)(40). Similar cytokine and chemokine profiles have also been detected in plasmas from children infected with A(H1N1)pdm09 virus (41), autopsy tissues from fatal cases of A(H1N1)pdm09 virus infection (42), and the lungs of pigs (43) This study demonstrated a remarkable consistency in the cytokine and chemokine patterns in the URT following infection with seasonal influenza A and B viruses.…”
Section: Discussionsupporting
confidence: 91%
“…2A-B). Effector cells such as macrophages, neutrophils and NK cells are recruited into the lungs as part of the innate immune responses [14]; here, histopathological examination showed that the deficit of CXCL14 did not alter the localization of the inflammatory infiltrate and its extent was neither increased or diminished ( Figure 2C). Despite the local upregulation of CXCL14 during viral infection [12], CXCL14 does not seem to have a pivotal role in regulating the inflammation in the lung, a process that is governed by a different subset of cytokines and chemokines.…”
Section: Cxcl14 Deficiency Does Not Impact the Outcome Of Influenza Imentioning
confidence: 79%
“…Detailed information about the infection procedures, clinical data and the results of the microarray and NGS analysis were previously published by our group [17]. A total of four lung tissue samples from days 1, 3, 5 and 14 post-infection, respectively, were selected for analysis by deep sequencing.…”
Section: Ferret Virus Infection and Sample Collectionmentioning
confidence: 99%
“…Adaptor sequences were removed and those reads with more than 10% Q<20 bases were filtered out. The resulting short-reads were uploaded to the Sequence Read Archive (accession# SRA048986) and they are publicly available [17].…”
Section: Ferret Virus Infection and Sample Collectionmentioning
confidence: 99%